The Challenge for Cause Procedure in Canadian Criminal Law - Regina A. Schuller; Caroline Erentzen (Oñati Socio-Legal Series)
There is a longstanding presumption in Canadian law that jurors will act impartially in carrying out their duties, but this presumption may be challenged when the defendant is a member of a racialized minority group. In those circumstances, the defence may initiate a challenge for cause procedure, wherein potential jurors are questioned about their ability to set aside any racial prejudice and judge the case solely on the evidence. Although the challenge for cause procedure has been in place for some time, little attention has been given to the process and whether it in fact effectively screens for juror bias. This article provides an overview of the challenge for cause procedure, with particular attention to race-based challenges, as well as psychological research assessing the effectiveness of the procedure. Reference is made to the authors’ analysis of actual jury selection proceedings in which the challenge procedure was invoked. The data revealed that, although only a small percentage of potential jurors admitted to potential prejudice in open court, many more were excluded by triers and counsel.